Implementation of Google Forms as Alternative for Quality Indicator Recording and Reporting Systems in the Time of Covid-19 Pandemic - Octavianus, Marshal; Indriani, Wiwin; Fitriasari, Nikma (Jurnal Kedokteran Brawijaya, 2022)
Recording and reporting are parts of health services aiming to create administrative discipline to improve health service quality. Covid-19 pandemic prevalence has impeded unit quality indicator recording and reporting, causing suboptimal quality measurements. This study aimed to see the implementation of Google Forms as a solution to overcome obstacles in unit quality indicator recording and reporting. This study was a one-group pre-experimental with a pre-and post-intervention design without control. The sample was seven people who were Laboratory Unit staff of a Private Hospital in Batu City. The results showed that applying Google Forms can provide staff's ability and timeliness in measuring unit quality indicators. A good quality measurement method can increase the effectiveness of monitoring and evaluation related to patient-centered quality improvement.